2018
DOI: 10.1111/bioe.12543
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the challenge for expedient ethical review of research in disasters and disease outbreaks

Abstract: Guideline 20 of the updated International Ethics Guidelines for Health‐related Research Involving Humans (2016) by the Council for International Organizations of Medical Sciences (CIOMS) provides guidance on research in disasters and disease outbreaks against the background of the need to generate knowledge quickly, overcome practical impediments to implementing such research, and the need to maintain public trust. The guideline recommends that research ethics committees could pre‐screen study protocols to exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…However, in Schuklenk's view the claim that the principles in the document are regarded as universal is seriously undermined by their 'demonstrably problematic production process' (Schuklenk, 2017: 172). 18 See, for example, Aarons (2019) for a critique of CIOMS guideline 20, which makes recommendations for pre-evaluation of proposals to be mobilised in emergency or disaster situations: informed by the situation in the Caribbean, Aarons proposes alternative plans for such situations. See also Barugahare and Kutyabami (2019), who question the absence of East African voices in the revision of the CIOMS guidelines, but also observe that, given their generality, there is scope for local and regional interpretation and application of these.…”
Section: Discussionmentioning
confidence: 99%
“…However, in Schuklenk's view the claim that the principles in the document are regarded as universal is seriously undermined by their 'demonstrably problematic production process' (Schuklenk, 2017: 172). 18 See, for example, Aarons (2019) for a critique of CIOMS guideline 20, which makes recommendations for pre-evaluation of proposals to be mobilised in emergency or disaster situations: informed by the situation in the Caribbean, Aarons proposes alternative plans for such situations. See also Barugahare and Kutyabami (2019), who question the absence of East African voices in the revision of the CIOMS guidelines, but also observe that, given their generality, there is scope for local and regional interpretation and application of these.…”
Section: Discussionmentioning
confidence: 99%
“…The need for rapid, expedited ethics review of study protocols to facilitate a speedy investigation into disease pathogenesis as well as therapeutics and interventions required to curb the spread and impacts of the diseases was a crosscutting theme in the papers reviewed [60]. A central idea here entailed constituting ex-temporal committees or processes of review, including joint and multiple reviews [23,56] to reduce the propensity for long and duplicated reviews [3,4]. Such a framework, which allows for representatives of individual RECs to form part of the ad hoc committee, allows for a central review and approval process for which the final decision will be reported back via the same channel, thus reducing the time for the review of articles.…”
Section: Similarity Of Process(es) For Phes Ethical Research Governancementioning
confidence: 99%
“…At the core of this emphasis is the need for study protocols, and research review processes to strengthen, not minimise, important ethical principles -from respect for persons, the imperative to do no harm, maximise benefit and minimise risks under beneficence, to demonstrating fairness and justice particularly in the selection of study participants -during infectious disease outbreaks [66][67][68]. These findings are also captured in the broader literature on the implementation of research during pandemics and disasters [47,69,70], as well as the ethical considerations that researchers and sponsors must bear in mind in their design and implementation of studies that involve human subjects [4,43,65], especially those from vulnerable communities and populations [70].…”
Section: Relevance Of the Content Of Rec Reviews For Ethical Principl...mentioning
confidence: 99%
See 1 more Smart Citation
“…Future research/initiatives: Strengthen the relationships between humanitarian aid groups and academic institutions. [11,59] Research is justified insofar as it is not compromising relief efforts [60] MSF's refusal to participate in research on treatment rationing [55] The evolution form pure researcher to researcher-practitioner [61] Justification for research in conflict setting [62] Explanation of MSFs ethics of studying HIV medication rationing [63] Generally limited resources in these settings [64] Effective research design might inhibit optimal treatment initiatives [53] Reassessing a participant's consent during the experiment [44] Informed consent in the setting of a particularly fatal disease [46] Use of a "gatekeeper" when seeking informed consent [21] A more nuanced view of consent might be more suitable for emergencies [21] More flexible approach to consent [22] "Humanitarian misconception" [27] Challenges of consenting children [65] Consent during disasters may be coercive [23] Exclusion of groups may undermined justice [38] Regional collaboration for ethical review [66] Dynamic consent [38,44] Participants may find it difficult to separate consent for research from receiving aid [27,38,46] Use of gatekeepers for attaining consent [21] Acceptance of less rigid consent procedures in the humanitarian setting [21,22] Forcing participants to relive trauma for the purpose of research raises ethical questions [44,65] Unavoidable coercion [23] Tensions:…”
Section: Clinical Trialsmentioning
confidence: 99%